Perspectives of English learners and Teachers on the use of L1 in L2 classrooms - Kadhim, Adil Jawad (2016)
The main purpose of this research is to study closely the causes and the perceptions of students and teachers about using the students’ native language in English classrooms. Over the years, the discussion of whether to apply the first language or not was controversial. All the results of the literature review state that there are two opposing opinions: On the one hand, there are the supporters of using L1. They believe it facilitates the process of learning and teaching the second language. On the other hand, there are opponents of using L1. They believe there are several disadvantages. Because of the diversity of opinions, the researcher of this study became curious about this problem and decided to study it in the hope of coming out with useful results which could be helpful to other researchers and English instructors. This study was conducted in Abu Dhabi, in three private schools: Al Dhafra private schools, Al Etihad Private School and The International Community School. All the data were being collected through using classroom observations, questionnaires and interviews. The two research methods, qualitative and quantitative have been used to produce more precise, reliable and useful results. The findings showed that several English teachers and students prefer not to use L1 while studying L2 however they confess that they employ it in some certain situations and context, for example, to explain some difficult rules or topics in grammar, to use some new terms or expressions, to joke, to clarify meanings or improve students’ understanding.